DISEMINASI INOVASI TEKNOLOGI PERTANIAN MELALUI PORTAL WEB BADAN PENELITIAN DAN PENGEMBANGAN PERTANIAN - Gartina, Dhani (Sekretariat Badan Penelitian dan Pengembangan Pertanian, 2015)
The Indonesian Agency for Agricultural Research and Development (IAARD) has the mandates of creating and disseminating agricultural technology innovations. The dissemination process of the agricultural technology innovations has not yet been maximized, and consequently not many people (farmers) can benefit from the R&D results. Technology innovation dissemination through a web portal has become IAARD’s choice. Problems related to dissemination through a web portal is in the method of presenting and managing the information in the web site. This research aimed to determine the benefits of dissemination of agricultural technology innovation through web site and policy strategies for the development of Balitbangtan web portal in the future. This research used a descriptive method to review the use of the web portal by the visitors, as a medium for the dissemination. The analysis included the number of visitors, profile of the visitors, information search and questions submitted by visitors. The study showed that the amount of information presented every year increased, but the number of visitors tended to decrease. The use of information given in the web portal was only dominated by students and private sectors. Java Island tended to dominate the origin of visitors. Packaging of the information of agricultural technology innovation can only be understood by researchers. Information support from researchers/extensions/engineers needs to be improved. A well-developed communication between the source of information and the user has not yet been established. The development of IAARD web portal needs to pay attention on philosophy, science, and art.